Nucleo-cytoplasmic interactions affecting biological performance of Lipaphis erysimi in Brassica juncea - Singh, Naveen; Dhillon, Mukesh K. (Frontiers in Plant Science, 2022)
Hybrids have been successfully used to improve crop productivity, including Brassicas. Nucleo-cytoplasmic interactions have been reported to influence the expression of resistance to insect pests in several crops. We studied the effects of Cytoplasmic Male Sterility (CMS) in Brassica juncea carrying alien cytoplasms and their respective maintainer (B) lines on the antibiosis mechanism of resistance, involving development, survival, reproduction potential and population build-up of mustard aphid, Lipaphis erysimi, and the levels of defense phyto-chemicals. Present findings revealed that the numbers of aphids/plant, aphid multiplication rate and aphid resistance index were lower on ber CMS under natural, mori CMS under artificial infestation conditions, and juncea under both the test conditions indicating nucleo-cytoplasmic interactions for aphid reaction. Across cytoplasms, nymphal, reproductive and total developmental periods were significantly longer on SEJ 8, NPJ 161, LES 39, and NPJ 93, while the reproductive potential and survival were lower on PM 30, Pusa Tarak and SEJ 8 as compared to other nuclear backgrounds. Across nuclear backgrounds, nymphal, reproductive and total developmental periods were significantly longer on ber CMS, while reproductive potential and survival were lower on ber and mori CMS as compared to other cytoplasms. Total glucosinolates were significantly greater and myrosinase lower in Pusa Agrani, SEJ 8, LES 39, PM 30, NPJ 112, and Pusa Tarak as compared to the other nuclear backgrounds. Furthermore, total glucosinolates were significantly greater and myrosinase lower in ber CMS and juncea as compared to other cytoplasms. The studies suggest that CMS as well as cytoplasmic and nuclear gene interactions regulate the expression of defense compounds such as glucosinolates and determine the expression of resistance/susceptibility to L. erysimi. These findings shall help in identification of suitable L. erysimi tolerant nucleo-cytoplasmic combinations for their deployment in B. juncea hybrid breeding program.